2015
DOI: 10.1200/jco.2014.59.4812
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil, Leucovorin, and Irinotecan Plus Cetuximab Treatment and RAS Mutations in Colorectal Cancer

Abstract: In the first-line treatment of mCRC, patients with RAS wild-type tumors derived a significant benefit from the addition of cetuximab to FOLFIRI; patients with RAS tumor mutations did not. Molecular testing of tumors for all activating RAS mutations is essential before considering anti-epidermal growth factor receptor therapy, thereby allowing the further tailoring of cetuximab administration to maximize patient benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
580
6
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 725 publications
(624 citation statements)
references
References 20 publications
28
580
6
10
Order By: Relevance
“…Auch diese Evaluation zeigte, dass Cetuximab bei RAS-mutierten Tumoren nicht wirksam war, allerdings wurde hier kein negativer Einfluss auf Effektivitäsparameter beobachtet [1042].…”
Section: Ras-mutationunclassified
See 1 more Smart Citation
“…Auch diese Evaluation zeigte, dass Cetuximab bei RAS-mutierten Tumoren nicht wirksam war, allerdings wurde hier kein negativer Einfluss auf Effektivitäsparameter beobachtet [1042].…”
Section: Ras-mutationunclassified
“…Quellen: [1109] Konsens Hintergrund Anti-EGFR-Antikörper zeigen keine Effektivität bei Vorliegen einer RAS-Mutation und sollen daher nicht eingesetzt werden [1041,1042,1045]. Prospektive Untersuchungen, welche die Effektivität von anti-VEGF-Substanzen in der Erstlinientherapie von Tumoren mit RAS-Mutation untersuchen, liegen nicht vor.…”
Section: Level Of Evidence 3aunclassified
“…RAS mutations, including both KRAS and NRAS gene mutations, have been reported in about 50% of primary CRC, and have been associated with resistance to the anti-epidermal growth factor receptor (EGFR) monoclonal antibodies (MoAbs), Cetuximab and Panitumumab, in the metastatic disease (Rizzo et al, 2010;Bronte et al, 2011). This has been well exploited by several randomized trials (De Roock et al, 2010;Bokemeyer et al, 2012;Douillard et al, 2013;Heinemann et al, 2014;Schwartzberg et al, 2014;Van Cutsem et al, 2015;Bokemeyer et al, 2015), that have overall shown significant poorer response rates and inferior survival outcomes in RAS-mutated patients receiving chemotherapy plus anti-EGFR MoAbs, compared to RAS-wild type population. RAS mutations represent the only, molecular, predictive biomarker approved for clinical use, while their prognostic role is still debated.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have demonstrated that other RAS mutations (exons 3 and 4 of KRAS and exons 2,3 and 4 of NRAS) are predictive of resistance to anti-EGFR drugs (3,4). These findings led most of the regulatory agencies and the major clinical guidelines to restrict the use of cetuximab and panitumumab to patients with wild-type RAS (including KRAS exons 2/3/4 and NRAS exons 2/3/4) tumors.…”
Section: Introductionmentioning
confidence: 99%